Performance evaluation and prediction of first lactation milk yield in Vrindavani cattle - CHANDRAKAR, JHARNA; KUMAR, AMIT; NASKAR, S; GAUR, G K; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2019)
The present investigation was carried out using first lactation milk records of 1,084 Vrindavani cows spread over a period of 17 years (2000–2017). The overall performance, effect of non-genetic factors on the first lactation test day (TD) milk yields, age at first calving (AFC), first lactation length (FLL), first lactation peak yield (FLPY), first lactation average daily yield (FLADY), first lactation 305 days milk yield (FL305MY) and first lactation total milk yield (FLTMY) were investigated. The overall least squares mean for FL305MY, FLTMY, FLADY and FLPY were 2825.86±26.04, 2883.40±35.91, 8.48±0.07 and 14.37±0.11 kg, respectively. The effect of season was highly significantly affecting AFC, FLADY, FLPY, FLTMY, FLL and all the test day milk yields. The influence of period was highly significant on AFC, FL305DMY, FLTMY, FLL, FLPY, FLADY, all the test day milk yields. The heritability estimates of FL305DMY, FLTMY and test day milk yields were low to moderate. While predicting FL305MY, the highest coefficient of determination (R2) was obtained for TD96. However, while predicting FLTMY, the highest R2 value was observed for TD246.